The Influence of Genetics and Gene Polymorphism on Biological Complications for Dental Implant Survival: A Review - Januzzi, Marcella Santos [UNESP]; Dos Santos, Daniela Micheline [UNESP]; Del Rei Daltro Rosa, Cleber Davi [UNESP]; Turcio, Karina Helga Leal [UNESP]; De Moraes Melo Neto, Clóvis Lamartine [UNESP]; Da Silva Fernandes, Maria Eduarda [UNESP]; De Magalhães Bertoz, André Pinheiro [UNESP]; Adriazola Ique, Manuel Martin [UNESP]; Goiato, Marcelo Coelho [UNESP] (Thieme, 2024)
The objective of this review is to expose the main genetic changes and genetic polymorphisms that may or may not be associated with greater susceptibility to reduced survival of dental implants and, consequently, to their loss. Case-control studies that fully portrayed the specific types of genetic polymorphisms that may be associated with dental implant failure were included by searching in the PubMed, Scopus, and Web of Science databases from 2010 to 2023. The following descriptors and their combinations in English were used to search for articles: dental implants, bone genes, genetics, polymorphism genetics, genetic risk factor, and interleukin. The initial search resulted in 107 results (PubMed n = 47, Scopus n = 14, and Web of Science n = 46). After a manual search, reviewing each article's title and abstract, and excluding duplicates, systematic reviews, and literature reviews, 30 articles were selected. After reading these 30 articles in full, 18 studies that did not describe the specific genetic polymorphism in relation to dental implant survival were excluded. Therefore, 12 articles were included in this review. The genetic polymorphisms of interleukin (IL)-1A, IL-1B, IL-4, IL-6, IL-10, IL-1 receptor antagonist, tumor necrosis factor-α, receptor activator of nuclear factor kappa B legend, and cluster of differentiation 14 were analyzed in the included studies. In seven of the studies, a statistically significant correlation between genetic polymorphisms and dental implant failure was observed. Of the polymorphisms studied, IL-1A (-899), IL-1B (+3954), and IL-4 (+33) showed a greater association with dental implant loss.
Keywords: dental implants; genetic polymorphism; genetic risk factor; genetics; interleukins